Determining reference ranges for immunological cells of healthy indigenous individuals from a region in Brazil - Isa Rita Brito de Morais; Dyjaene de Oliveira Barbosa; Gabriel Barroso de Almeida; Regina Rossoni da Costa; Bruna Oliveira da Silva; Laís Albuquerque de Oliveira; Julia Pimentel Arantes; Layla Oliveira Campos Leite; Luana Rossato; Marcos Borges Ribeiro; Silvana Beutinger Marchioro; Songelí Menezes Freire; et al. (Einstein (São Paulo), 2023)
ABSTRACT Objective The establishment of reference values for a subset of leukocytes is common in clinical practice, and ethnic variations are strongly associated with disease development. In Brazil, indigenous people are vulnerable to infections, and few studies have described the health and disease conditions of this population. This study aimed to provide reference values for immunological cell subsets in indigenous Brazilians living in the state of Mato Grosso do Sul. Methods Flow cytometry and 4-color combinations of monoclonal antibodies were used to characterize cells. A total of 115 healthy adults, mostly females (72%), were included in the study. The results are presented as mean and median (2.5%-97.5% percentiles) for T and B lymphocytes, CD4+ T cells, CD8+ T cells, Natural Killer cells, monocytes, and dendritic cells, providing an average immunological profile for the population in question. Results The relative medians of CD3+, CD4+, and CD8+ T cells were significantly higher in women than in men in a healthy indigenous population. Conclusion To our knowledge, cell reference data from indigenous Brazilians are unknown in the literature. The immune cell results presented in this pioneering study will contribute to the clinical and laboratory evaluation of the Brazilian indigenous population, especially given the important differences when compared with other Brazilian ethnic groups.